2003
DOI: 10.1523/jneurosci.23-08-03118.2003
|View full text |Cite
|
Sign up to set email alerts
|

Small GTPase Cdc42 Is Required for Multiple Aspects of Dendritic Morphogenesis

Abstract: The study of dendritic development in CNS neurons has been hampered by a lack of complex dendritic structures that can be studied in a tractable genetic system. In an effort to develop such a system, we recently characterized the highly complex dendrites of the vertical system (VS) neurons in the Drosophila visual system. Using VS neurons as a model system, we show here using loss-of-function mutations that endogenous Cdc42, a member of Rho family of small GTPases, is required for multiple aspects of dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 39 publications
(44 reference statements)
3
93
0
1
Order By: Relevance
“…Recent work (Czuchra et al, 2005) has shown that the transfection of Cdc42-null fibroblastoid cells with a Cdc42 dominant-negative mutant (N17 cdc42) elicits additional phenotypes that are not present in untransfected Cdc42-null fibroblasts. This observation raises important questions about the specificity of Rho GTPase dominant-negative approaches and is in line with previous reports showing that dominant-negative mutant expression induced more severe phenotypes than those produced by genetic loss-of-function approaches on identical cell types or organisms (Luo et al, 1994;Scott et al, 2003). Therefore, the use of conditional tissue-specific gene ablation techniques provides a stringent system for studying the roles of Rho GTPases at cellular, tissue, and organism levels.…”
Section: Cdc42 Is Not Required For Opc Proliferation Directed Migratsupporting
confidence: 84%
“…Recent work (Czuchra et al, 2005) has shown that the transfection of Cdc42-null fibroblastoid cells with a Cdc42 dominant-negative mutant (N17 cdc42) elicits additional phenotypes that are not present in untransfected Cdc42-null fibroblasts. This observation raises important questions about the specificity of Rho GTPase dominant-negative approaches and is in line with previous reports showing that dominant-negative mutant expression induced more severe phenotypes than those produced by genetic loss-of-function approaches on identical cell types or organisms (Luo et al, 1994;Scott et al, 2003). Therefore, the use of conditional tissue-specific gene ablation techniques provides a stringent system for studying the roles of Rho GTPases at cellular, tissue, and organism levels.…”
Section: Cdc42 Is Not Required For Opc Proliferation Directed Migratsupporting
confidence: 84%
“…The high ROS cells appeared to be migratory cells, and ROS may impact intracellular processes that are crucial for process extension and cell migration. For example, several studies have implicated ROS in the regulation of GTPases that are known to be important for the cytoskeletal rearrangements necessary for cell migration and for dendritic morphogenesis (Deora et al, 1998;Kheradmand et al, 1998;Moldovan et al, 1999;Puceat, 2005;Scott et al, 2003;Werner and Werb, 2002). Additional studies on the connection between ROS levels and GTPase activity may reveal how both influence cell shape.…”
Section: Discussionmentioning
confidence: 99%
“…Neither the expression of Cdc42 mRNA (F (2,15) = 0.03, P = 0.97) nor of Duo mRNA (F (2,15) = 0.1, P = 0.91) differed across these three groups of animals ( Figure 5). …”
Section: Laminar Analysis Of Mrna Expressionmentioning
confidence: 95%
“…In neuronal cultures, Cdc42 is essential for the establishment of the full complement of dendritic spines. [13][14][15] Similarly, Rac1 (Ras-related C3 botulinum toxin substrate 1) helps stabilize the actin cytoskeleton, and thus appears to contribute to dendrite initiation, elongation and branching, as well as the outgrowth of spine-like structures, 13,14 In hippocampal slice preparations, Rac1 has been shown to be a critical regulator of dendritic spine density. 16 In contrast, RhoA (Ras homologous member A) regulates the destabilization of the actin cytoskeleton, such that the activation of RhoA results in decreased dendritic growth and branching and a reduction in the density of dendritic spines.…”
Section: Introductionmentioning
confidence: 99%